A Case Study on the Personal Problems of Seventh-Grade Students at Adisucipto Catholic Junior High School Kupang - Antonia Erlanda Tae; Wens Nagul; Petronela Teme (The Future of Education Journal, 2025)
This study aims to describe the personal problems experienced by a seventh-grade student at SMP Katolik Adisucipto Kupang, identified as LAK, who exhibits symptoms of low concentration during the learning process due to a physical health condition present since birth. The research employed a case study method through direct observation, interviews with subject teachers, the homeroom teacher, the school counselor, parents, and siblings, as well as documentation analysis of academic records. The findings reveal that the student frequently disturbs classmates, is restless in class, shows a lack of focus, and experiences a decline in academic performance. The contributing factors include internal aspects such as boredom and low motivation, and external factors such as peer influence and the student’s physical health condition. Interventions were provided through individual counseling using a behavioral approach, including the development of a daily study schedule, the application of time management techniques using the Pomodoro Method, and efforts to raise the student’s awareness to change learning behaviors. The results indicate that the intervention has the potential to improve the student's concentration and learning discipline, although continued monitoring by the school counselor, homeroom teacher, and subject teachers remains necessary. This study highlights the importance of behavioral counseling techniques in addressing learning problems among students with special needs related to concentration management.